Izin Poligami dalam Tinjauan Fikih dan Hukum Positif di Indonesia - Trigiyatno, Ali (Al-Manahij: Jurnal Kajian Hukum Islam, 2009)
The government defined some norms on doing polygamy considering its negative effects. One of the requirements is a license for doing polygamy from the Religious Court. This letter of permission contains some benefits for the family especially protecting the right of the children and the wife.